Association of maternal oral health-related knowledge, attitude, and socioeconomic status with dental caries status of preschoolchildren in Belgaum City: A cross-sectional study - Nishant Mehta; Anil Ankola; Nitika Chawla; Ladusingh Rajpurohit (Wolters Kluwer Medknow Publications, 2019)
Background: Oral health status is dependent on the interplay of multiple etiological and predisposing factors, which have varying ability to cause diseases. However, little is known about maternal factors associated with the oral health of preschoolchildren at different stages of their development. Aim: To assess the association of maternal oral health-related knowledge and attitude with the preschoolchildren's dental caries status. Materials and Methods: The present study was a cross-sectional study conducted among 618 mother-child pairs. Three to 5-year-old preschoolchildren were selected from eight preprimary schools following two-stage random sampling. Responses from the mothers on oral health-related knowledge and attitude were collected through a structured questionnaire. It was followed by dental caries examination of their preschoolchildren based on the WHO criteria for dental caries examination. Chi-square test was done to find the association between the study variables. Model for the prediction of dental caries occurrence in preschoolchildren was generated following multiple logistic regression analysis. Level of significance was set at P < 0.05. Results: The mean correct oral health-related knowledge and attitude scores of mothers were 6.59 ± 2.35 and 7.28 ± 1.83, respectively. Preschoolchildren had a mean untreated dental caries score of 2.73 ± 1.63 and decayed, missing, and filled teeth score of 3.13 ± 1.79. Untreated dental caries in children was found to be statistically significantly associated with maternal oral health-related knowledge ( P = 0.021) and attitude ( P = 0.006). Mothers who were having better knowledge and favorable attitude toward oral health had significantly lower odds of developing dental caries in their children as reflected by the logistic regression analysis (odds ratio = 0.33 [0.22-0.52] and 0.36 [0.24-0.53], respectively). Conclusion: The study concluded that maternal factors were significantly related to children's dental caries status and emphasized the need of raising awareness among mothers for limiting and controlling dental caries among preschoolchildren.